Chronology of a Holocene Core From the Pearl River Delta in Southern China - Xu, XiaoLin; Li, HongWei; Tang, LinJie; Lai, ZhongPing; Xu, GuanJun; Zhang, XianHe; Wang, YiXuan (Frontiers in Earth Science, 2020)
Establishing a reliable chronological framework for sediments is crucial to the reconstruction of evolution process of estuarine delta, and the study of regional paleoenvironmental history, e.g., sea level fluctuations due to global climatic changes. High resolution chronology is still very limited for Holocene sediments in the Pearl River delta (PRD) in southern China. This study tries to construct a detailed chronology for core DA of 37.7 m in depth by using luminescence (seven samples) and radiocarbon (fourteen samples) dating techniques. Our results indicate that both luminescence and radiocarbon dating methods are suitable for the Holocene sediments in the PRD and that sediments of core DA were deposited during 7.3–0.18 ka. The 14C age is generally older than the OSL age for the sediment at the similar depths, and the age difference increased from 0.45 ka at the depth of 21 m to 0.98 ka at the depth of 35 m. The reason that 14C ages are relatively older might be caused by the carbon-reservoir effect which requires further study. The sedimentation rate increased from 3.74 m/ka during 7.3–2 ka to 7.92 m/ka in the last 2 ka. The appearances of rusty stains in upper unit of the core revealed that the water level was gradually falling. After the formation of underwater sand body at about 2 ka, the sediment was subject to continuous shifting between submergence and exposure.